Inheritance of house unit on Waqf land from Islamic and Malaysian law perspectives - Baharudin, Mohammad Hidir; Ahmad Sarkawi, Azila; Mohyin, Nur Affah (Asian Economic and Social Society (AESS), 2021)
Waqf is considered as an important financial source in Islam. In Malaysia, waqf is held under the Department of Wakaf, Zakat, and Hajj (JAWHAR) at the federal level and the State Islamic Religious Council (SIRC) of the respective states for the state level. As the Malaysian population is growing nowadays, it has become necessary to develop waqf land into housing development. However, this research found that there are no specific works of literature on the concept of inheritance of housing units built on waqf land in Malaysia. Hence, this research aims to examine the concept of inheritance and waqf in Islamic law and Malaysian law, as well as waqf housing projects in Malaysia. This research is based on a qualitative and descriptive cross-sectional analysis through the governing statutes. The discussion from the Islamic perspective will be based on the Holy Quran, the traditions of the Prophet (PBUH), and the examination of the views of Muslim jurists of four well-known schools of law as well as the views of contemporary Muslim scholars. The research found that the inheritance of housing units on waqf land complies with Islamic law and Malaysian law. Its leasehold status makes it perpetual and inalienable, which coincides with the concept of waqf in Islam.